Loneliness and Migraine Self-Management: A Cross-Sectional Assessment - Jacob Z. Lui; Nathan P. Young; Jon O. Ebbert; Jordan K. Rosedahl; Lindsey M. Philpot (SAGE Publishing, 2020)
Background: Chronic illness is often comorbid with the psychological state of loneliness. Models of care for patients who experience chronic migraines may often lack an understanding of psychosocial influences of the illness. Addressing the effects of loneliness on the health behaviors of chronic migraine patients may further elucidate gaps in care that exist beyond the biomedical approach to migraine treatment. The primary aim of this study was to assess the relationship between loneliness and behavioral health decisions in chronic migraine patients, specifically patient ability to self-manage, and effectiveness of treatments. Methods: We conducted a cross-sectional survey among patients (n = 500) with migraine and assessed for the experience of loneliness by using the University of California, Los Angeles-Revised (UCLA-R) Three-item Loneliness Scale and the extent of migraine-related disability via the Migraine Disability Assessment (MIDAS). Furthermore, we evaluated patients for their ability to self-manage their migraines, and perceived effectiveness of treatment. Results: Nearly half of our population reported at least one measure of loneliness (230/500, 46.0%). Patients experiencing chronic migraine were statistically more likely to report feeling lonely when compared to patients with episodic migraines ( P < .001). Patients who report loneliness had lower odds of feeling 'very satisfied" with their ability to self-manage their migraine symptoms (aOR = 0.34, 95% CI 0.14-0.81) and had lower odds of feeling "very satisfied" with their ability to avoid conditions that cause their headache (aOR = 0.39, 95% CI 0.16-0.91). Conclusions: Loneliness has significant effects on the illness experience of patients with chronic migraines, including their ability to self-manage or be satisfied with their current state of care. Psychosocial models of care that address loneliness among patients with chronic migraine may help improve health outcomes and management.